The blind men and the elephant: The case for a transdiagnostic approach to initiation - Buckle, Karen Leneh; Poliakoff, Ellen; Gowen, Emma (Frontiers in Psychology, 2023)
Difficulty initiating voluntary action is an under-recognized and often invisible impairment in various psychiatric, neurodevelopmental, and neurological conditions. Understanding the commonalities of volition impairments across diagnoses is limited by a lack of consistent terminology, arbitrary distinctions between conditions, the habit of looking only to the prevailing definitions and theories to explain observed traits, and the covert nature of initiation. The siloed approach to research in this area evokes the parable of the blind men and the elephant, where understanding the whole picture is impeded by a limited view. There has been little effort to consider how differing terms overlap or to use objective methods to differentiate phenomena along meaningful lines. We propose a triad of interacting elements, all of which are needed for successful initiation of voluntary action: (i) executive function, (ii) volition, and (iii) movement. Failure to initiate a response may be due to impairments in any of these, which often co-occur. This paper calls for the following considerations to improve research in this area: (i) put aside preconceptions about conditions and their mechanisms to adopt a flexible transdiagnostic approach; (ii) consider executive function, movement, and volition as possible dimensional variations with related underlying mechanisms; (iii) carefully differentiate components of complex functions; (iv) look to first-hand reports for covert and previously unrecognized traits. These approaches have the potential to elucidate the cognitive and biological mechanisms underpinning voluntary action and create a foundation to develop more appropriate and informed interventions.